(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
The purpose of this paper is to discuss the thematic of customer-centered quality in academic libraries and contribute to the importance of quality evaluations based on the perception of their customers for this type of library. It is especially important in Brazil, where evaluations of higher education institutions and their infrastructure items, including libraries, are compulsory. It highlights a specific methodology, the LibQUAL+®, created in the United States and used in hundreds of libraries around the world, but without any perceptible application in Brazil as yet. From the analysis of LibQUAL+® assessment procedures, the article aims to present the benefits that can be achieved from the application of this methodology as well as it intends to verify the possibilities of using it in academic libraries in Brazil. It concludes that the methodology presents aspects which can support the academic library management, as identifying strong and weak points of the services, becoming closer to the library´s customers’ needs, comparing the library performance with other libraries and defining the best practices in the field, besides contributing to a more professional management of the libraries. Keywords: Academic Libraries. Customer Services. Quality. Customer Satisfaction. LibQUAL+®. Link para o texto completo (PDF) http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/3117/2402